Regulation of Tyrosine Hydroxylase Activity in Cultured Mouse Neuroblastoma Cells: Elevation Induced by Analogs of Adenosine 3′:5′-Cyclic Monophosphate - Waymire, J. C. (1972)
Mouse neuroblastoma cells in culture have been used as a model for the study of the mechanism by which activities of tyrosine hydroxylase (EC 1.14.3.a) are regulated in sympathetic tissue. The activity of tyrosine hydroxylase in cultured cells drops to barely detectable activities after 1 week and remains low for months in culture in the uncloned cell line of neuroblastoma. Activity in an adrenergic clone isolated from the uncloned line has about 20% of the activity of the fresh grated tumor cell. N(6), O(2′)-dibutyryl adenosine 3′:5′-cyclic monophosphate causes a concentration and time-dependent increase in enzyme activity in both the cloned and uncloned cell lines. Enzyme activity is elevated by other stable analogs of adenosine 3′:5′-cyclic monophosphate, notably the N(6)-monobutyryl, 8-aminomethyl, and 8-methylthio derivatives of the cyclic nucleotide; by the inhibitor of cyclic nucleotide phosphodiesterase, papaverine; and by sodium butyrate. Changes in cell morphology and tyrosine hydroxylase activity are shown not to be necessarily related.